2020
DOI: 10.1186/s12894-020-00634-1
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in sexual health in bladder cancer patients: a systematic review of the evidence

Abstract: Background: Bladder cancer (BC) treatment can have a detrimental effect on the sexual organs of patients and yet assessment of sexual health needs has been greatly overlooked for these patients compared to those who have undergone other cancer therapies. Methods: This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines in July 2019. Studies were identified by conducting searches for Medline (using the PubMed interface), the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
0
30
0
1
Order By: Relevance
“…Phase 1 of the modified MRC framework resulted in 3 published literature reviews. 12 14 In the mental wellbeing literature review, no mental wellbeing interventions specifically designed for BC patients were identified, and so our systematic review for this topic was extended to assess mental wellbeing interventions for all urological cancer types—with a specific focus on reported endpoints as well as the structure and type of the interventions. In this literature review we found that couple base interventions provided the best results, and depression was the most commonly reported endpoint.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phase 1 of the modified MRC framework resulted in 3 published literature reviews. 12 14 In the mental wellbeing literature review, no mental wellbeing interventions specifically designed for BC patients were identified, and so our systematic review for this topic was extended to assess mental wellbeing interventions for all urological cancer types—with a specific focus on reported endpoints as well as the structure and type of the interventions. In this literature review we found that couple base interventions provided the best results, and depression was the most commonly reported endpoint.…”
Section: Resultsmentioning
confidence: 99%
“…There is a lack of consistent measures to assess sexual wellbeing in BC patients; in particular, there is a lack of validated questionnaires with appropriate psychometrics and social measures. 12 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If patients require chemotherapy, testicular sperm extraction is recommended prior to treatment. Total cystectomy can also affect fertility by causing ejaculation failure, so after treatment, patients will also require testicular sperm extraction for reproduction [ 12 ].…”
Section: Resultsmentioning
confidence: 99%